2019
DOI: 10.1186/s12985-019-1142-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of high EEHV antibody seroprevalence and spatial variation among captive Asian elephants (Elephas maximus) in Thailand

Abstract: BackgroundElephant endotheliotropic herpesviruses (EEHV) can cause an acute highly fatal hemorrhagic disease in young Asian elephants (Elephas maximus), both ex situ and in situ. Amongst eight EEHV types described so far, type 1 (subtype 1A and 1B) is the predominant disease-associated type. Little is known about routes of infection and pathogenesis of EEHV, and knowledge of disease prevalence, especially in range countries, is limited.MethodsA large cross-sectional serological survey was conducted in captive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 25 publications
(31 reference statements)
4
31
4
Order By: Relevance
“…Previous studies relied on an EEHV gB ELISA to show that 80% of elephants in North America and Europe and 42% within a large group of elephants tested in Thailand were seropositive for EEHV infection (8,9). In our study, in contrast, 100% of healthy adult elephants had evidence of prior EEHV infection.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Previous studies relied on an EEHV gB ELISA to show that 80% of elephants in North America and Europe and 42% within a large group of elephants tested in Thailand were seropositive for EEHV infection (8,9). In our study, in contrast, 100% of healthy adult elephants had evidence of prior EEHV infection.…”
Section: Discussioncontrasting
confidence: 50%
“…The results showed that as many as 80% of elephants tested in North American and European zoos were EEHV seropositive. A follow-up study using the same assay determined a seroprevalence of 42.3% among captive Asian elephants in Thailand (9). Because gB is relatively well conserved, the possibility that serologic responses detected against the protein can distinguish among infections with the different EEHVs endemic within Asian elephant populations appears remote.…”
mentioning
confidence: 99%
“…Van den Doel et al, (2015) designed an EEHV-specific ELISA with E. coli -expressed EEHV1A glycoprotein B (gB) as the antigen [ 12 ]. This assay has been used to test two large cohorts of elephant sera and showed that 37% of elephants from Western zoos [ 12 ] and 42% of captive elephants in Thailand [ 13 ] were seropositive for EEHV. Although it was shown that EEHV infections were relatively wide-spread, 24% of the elephants with PCR-confirmed EEHV infection were designated EEHV seronegative in this assay [ 12 ], indicating that this assay probably underestimates EEHV seropositivity.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Van den Doel and coworkers showed that 37% of the European zoo elephants tested (N=125) were seropositive to EEHV (12), while in 2019 Angkawanish and coworkers reported that 42% of 994 Thai elephants living under human care were EEHV seropositive (13). Both serosurveys used the 'bacterial' gB ELISA, of which this study showed that it underestimates EEHV seropositivity as compared to the novel ELISAs (Fig.…”
Section: Discussionmentioning
confidence: 79%